The association between leptin and adiponectin, and metabolic syndrome components and serum levels of lipid peroxidation in bipolar disorder patients treated with lithium and valproic acid - Dolab, Neda; Kamkar, Mohammad Zaman; Amiriani, Taghi; Yuzugulen, Jale; Marjani, Majid; Marjani, Abdoljalal (Cell Press, 2020)
Background: The aim of study is to assess a relation between the adiponectin and leptin levels, and metabolic syndrome components and lipid peroxidation treated with Li and VPA in bipolar disorder patients and compared with controls. Materials and methods: 56 patients and 31 healthy controls were enrolled. The ATP III criteria were used to determine metabolic syndrome components. Leptin, adiponectin, lipid peroxidation and lipid profiles were measured. Results: Malondialdehyde in Li patients was higher than VPA patients. BMI, waist circumference (WC), triglyceride, malondialdehyde and adiponectin levels were increased, whereas HDL-cholesterol (VPA treated patients) and leptin were decreased in patients compared with controls. Leptin and adiponectin were correlated with WC, triglyceride and malondialdehyde in both groups. Adiponectin was correlated with HDL-cholesterol in VPA patients. Conclusion: Patients should be checked metabolic syndrome components, serum leptin and adiponectin level occasionally to prevent possible deficiency or pathologic increase of these parameters.
Keywords: Public health; Clinical genetics; Internal medicine; Laboratory medicine; Clinical research; Leptin; Adiponectin; Metabolic syndrome components; Lipid peroxidation; Bipolar disorder patients; Lithium and valproic acid